2020
DOI: 10.1186/s13223-020-00491-5
|View full text |Cite
|
Sign up to set email alerts
|

A single centre retrospective study of systemic reactions to subcutaneous immunotherapy

Abstract: Background Subcutaneous immunotherapy (SCIT) is the standard approach for treating patients with sensitizations to aeroallergens. However, immunotherapy can trigger severe systemic reactions if delivered inappropriately or to high risk patients. We sought to characterize and quantify SCIT systemic reactions requiring epinephrine administration during a 6-year period in a Canadian setting following the recommendations for components and dosages published in the 2010 Canadian Society of Allergy and Clinical Immu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Of the patients who experienced systemic reactions, 26 of 28 (92.9%) received epinephrine during their clinic visit, whereas 2 of 28 reactions (7.1%) occurred outside the 30-minute mandatory observation period, with administration of epinephrine occurring outside the clinic setting. 5 This is comparable to a review of 860 patients receiving either aeroallergen or venom SCIT from a single academic allergy and immunology center with multiple allergists over a 12-month period in 2019, which showed the incidence of systemic reactions requiring epinephrine was 10 in 4242 injections or 0.24% (all of these reactions resulted from aeroallergen SCIT). 6 The per capita incidence of epinephrine use for this study is unavailable.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Of the patients who experienced systemic reactions, 26 of 28 (92.9%) received epinephrine during their clinic visit, whereas 2 of 28 reactions (7.1%) occurred outside the 30-minute mandatory observation period, with administration of epinephrine occurring outside the clinic setting. 5 This is comparable to a review of 860 patients receiving either aeroallergen or venom SCIT from a single academic allergy and immunology center with multiple allergists over a 12-month period in 2019, which showed the incidence of systemic reactions requiring epinephrine was 10 in 4242 injections or 0.24% (all of these reactions resulted from aeroallergen SCIT). 6 The per capita incidence of epinephrine use for this study is unavailable.…”
Section: Resultssupporting
confidence: 59%
“…A single-center retrospective review of 380 patients from a community allergy and immunology clinic between 2011 and 2017 showed that the incidences of systemic reaction requiring epinephrine were 28 in 380 patients (7.4%) and 1 in 1047 injection visits (0.095%). 5 No number of patients who had dropped out or discontinued SCIT secondary to side effects during the study time frame was reported. Of the patients who experienced systemic reactions, 26 of 28 (92.9%) received epinephrine during their clinic visit, whereas 2 of 28 reactions (7.1%) occurred outside the 30-minute mandatory observation period, with administration of epinephrine occurring outside the clinic setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AEs were recorded in overall about 10% of patients. The range of local and systemic reactions reported from previous studies is as low as 1.5% 23 up to 17.9% 25–28 . This is not surprising, taking into account that patient selection, type of product, adjuvant and route of administration as well as intensity of follow‐up may affect safety outcomes and vary considerably.…”
Section: Discussionmentioning
confidence: 90%
“…The range of local and systemic reactions reported from previous studies is as low as 1.5% 23 up to 17.9%. [25][26][27][28] This is not surprising, taking into account that patient selection, type of product, adjuvant and route of administration as well as intensity of follow-up may affect safety outcomes and vary considerably. ADER is a multicenter registry that includes patients from 8 countries with different characteristics, a wide spectrum of AIT products and administration protocols.…”
Section: Discussionmentioning
confidence: 99%